Evaluation of Anti-inflammatory Effects of Cinnamic Acid Against Dextran Sodium Sulfate Induced Ulcerative Colitis in Male Mice - Ameer Hussein, Maysam; Hashim Zalzala , Munaf (Iraqi Journal of Pharmaceutical Sciences, 2023)
Inflammatory bowel disease (IBD) is a common chronic inflammatory disease of the gastrointestinal tract, including ulcerative colitis and Crohn's disease. ulcerative colitis (UC) disease is characterized by chronic, persistent, recurrent, and nonspecific intestinal ulcers and mucosal inflammation. This study investigated the protective effects of cinnamic acid on dextran sodium sulfate (DSS) induced ulcerative colitis in mice. Forty adult male mice were collected and randomly divided into five groups, group Ӏ received a suspension of distill water and poloxamer, and group ӀӀ received 3% DSS in drinking water for 7 consecutive days. Two treatment groups received an oral suspension of cinnamic acid 50 and 25 mg/kg respectively and 3% DSS in drinking water, for 7 consecutive days and the final group received an oral suspension of cinnamic acid 50mg/kg for 7 days without DSS in drinking water. after All the animals were euthanized on day eight. The sample was collected for analysis. DSS with cinnamic acid 50 mg/kg group revealed a significant (p<0.05) reduction in Tumor necrosis factor α, interleukin 6, nuclear factor-κB ,cinnamic acid 25mg/kg revealed a significant (p<0.05) reduction in Tumor necrosis factor α and nuclear factor-κB but not significant (p>0.05)reduction in IL-6 when compared to the model group. Histopathological examination showed a significant reduction of inflammatory signs in all cinnamic acid-treated groups when compared to the DSS model group.In conclusion, the treatment with cinnamic acid significantly decreased the levels of DSS-associated oxidative stress. This finding supports the idea that the use of this substance could be used as a potential therapy for patients with ulcerative colitis.